Humanitarian logistics: a disaster relief operations framework during pandemic Covid-19 in achieving healthy communities / Mazrul Hisyam Ab Malik, Emi Normalina Omar and Siti Noorsuriani Maon - Ab Malik, Mazrul Hisyam; Omar, Emi Normalina; Maon, Siti Noorsuriani (Faculty of Business and Management, UiTM Shah Alam, 2020)
High levels of coordination, cooperation, and collaboration between involved aid providers are needed for efficient logistics processes. In the immediate response phase, coordination, cooperation, and collaboration are firstly required when nongovernmental organizations (NGOs) assess the beneficiaries’ needs by sending field assessment and coordination teams into the disaster area. This research explores the Malaysian scenario of humanitarian logistics as well as the challenges in collaborations between government agencies and NGOs during disaster relief operations in Malaysia to achieve healthy communities during pandemic Covid-19. Thus, this study used past literature to propose a conceptual framework and identified two factors namely, trust and coordination as the key factors in the successful humanitarian logistics framework. In addition, the role of NGOs during a disaster is also important to reduce the burden on government agencies in managing the humanitarian aid distribution process. Collaboration between government and NGOs is pursued in the mitigation and long-term recovery phases, where decisions are taken with caution, and NGOs strategies are adjusted to others without time pressure. The most important driver for successful collaboration is trust. Coordination provisions will increase trust between agencies involved in disaster relief operations. Therefore, building trust between parties involved in certain tasks in disaster relief activities can be enhanced by adding up a contract agreement to ensure both parties will work efficiently and coordinate with the job and minimize the risk that could occur.